The Relationship Between Social Anxiety and Phubbing Behavior Among Public Senior High School Students in Sleman Regency - Shinta Dwi Sarlini; Sigit Sanyata (FKIP - Universitas Riau, 2026)
This study aims to determine the relationship between social anxiety and phubbing behavior among public high school students in Sleman Regency. This study is a correlation study. The study population consists of public high school students in Sleman Regency from 8 schools with a total of 4,492 students. A sample of 354 students was selected using proportional random sampling. Data collection methods used the SAS-A (Social Anxiety Scale for Adolescents) and the Phubbing Scale. Validity testing was conducted using Expert Judgment. The reliability test used the Cronbach's alpha technique, obtaining p=0.924 for the social anxiety variable and p=0.924 for the phubbing behavior variable. The data were analyzed using descriptive statistics and simple regression with the SPSS 22 For Windows program. The results showed a positive and significant relationship between social anxiety and phubbing behavior, with a correlation coefficient of 0.292 and a p-value <0.05, meaning that higher social anxiety was associated with higher phubbing behavior. Additionally, the coefficient of determination was 0.085, indicating that social anxiety contributed 8.5% to phubbing behavior. These findings indicate that social anxiety plays an important role in shaping students’ phubbing behavior and highlight the importance of preventive intervention programs in educational settings.